Possessed Voices : Aural Remains from Modernist Hebrew Theater - Abeliovich, Ruthie, 1978- (Book collections on Project MUSE., 2019)
"Audio recordings are a valuable tool for understanding historical theater, yet they have seldom been used in scholarship. Possessed Voices tells the intriguing story of a largely unknown collection of recordings preserving performances of modernist interwar Hebrew plays. Ruthie Abeliovich focuses on four case studies: a 1931 recording of The Eternal Jew (1919), a 1965 recording of The Dybbuk (1922), a 1961 radio play of The Golem (1925), and a 1952 radio play of Yaakov and Rachel (1928). The book traces the spoken language of modernist Hebrew theater as grounded in multiple modalities of expressive practices, including spoken Hebrew, Jewish liturgical sensibilities supplemented by Yiddish intonation and other vernacular accents, and in relation to prevalent theatrical forms. Abeliovich shows how these performances provided Jewish immigrants from Europe with a venue for lamenting the decline of their home communities and for connecting their memories to the present. Analyzing sonic material against the backdrop of its artistic, cultural, and ideological contexts, she develops a critical framework for the study of sound as a discipline in its own right in theater scholarship."--